Performance of the OEDO beamline. (December 2020) - Hwang, J W; Michimasa, S; Yamada, K; Ota, S; Dozono, M; Imai, N; Yoshida, K; Yanagisawa, Y; Kusaka, K; Ohtake, M; Matsushita, M; Ahn, D S; et al.
Abstract: The OEDO (Optimized Energy Degrading Optics for RI beam) beamline has been developed to obtain low-energy (10 – 50 MeV/u) RI beams by slowing down the secondary beams at RIBF, RIKEN. Such beams are useful probes to investigate nuclear structure by means of nucleon transfer and Coulomb excitation reactions. The beamline is designed to produce a well-focused beam of small energy spread with the help of the angle-tuneable wedge degrader and the radio-frequency deflector. The commissioning and first physics experiments using the OEDO beamline were carried out in 2017. OEDO successfully provided the energy-degraded beams of Se, Zr, and Pd. Its performance including the optics and transmission was evaluated using those experimental data and it functions properly as designed. We expect that our novel beamline shed a light on the experimental approaches involving nuclear reactions at several tens of MeV/u to expand our knowledge of nuclei far beyond the line of stability.